Coupling the TEB and Surfatm Models for Heat Flux Modelling in Urban Area: Comparison With Flux Measurements in Strasbourg (France) - Le Mentec, S.; Stella, P.; Najjar, G.; Kastendeuch, P.; Saudreau, M.; Ngao, J.; Améglio, T.; Colin, J.; Flick, D.; Personne, E. (Frontiers in Environmental Science, 2022)
This study presents the coupling of TEB (Town Energy Balance) and Surfatm models developed for energy exchange estimates for urban impervious and vegetation surfaces, respectively. Once coupled, the TEB-Surfatm model allows the estimate of radiative, sensible (H), and latent heat (LE) fluxes in urban areas accounting for urban vegetation. The modelled fluxes were compared with measurements performed in an urban garden. The model was able to reproduce the energy fluxes, but its performance varied. The variability of the model accuracy depended on the measurement footprint in link with the heterogeneity of the site characteristics: while the measurement footprint fitted with the area characteristics considered by the TEB-Surfatm model, the modelled H and LE fluxes presented a good agreement with the measurements. In the other cases, some overestimation and underestimation occurred, in link with different fractions of impervious surfaces or green spaces. The validation of the TEB-Surfatm model for energy fluxes is a first step, the second will be to include the pollutant exchanges since Surfatm is able to quantify the atmosphere-biosphere fluxes for numerous pollutants. It will allow the TEB-Surfatm model to quantify the impact of urban greening on the assessment of air quality in urban areas.